(untitled) (European Journal of Interdisciplinary Research and Development, 2022)
Higher education is one of the most effective ways of organizing life. It gives freedom of life choice, spiritual and material independence, forms a worldview and life goals, develops a person’s ability to adapt to a changing social situation, gives life resilience and harmonizes existence, which is especially important for young people with disabilities.